2015
DOI: 10.2337/dc15-1643
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Efficacy and Safety of the Glucagon Receptor Antagonist LY2409021 in Patients With Type 2 Diabetes: 12- and 24-Week Phase 2 Studies

Abstract: OBJECTIVEType 2 diabetes pathophysiology is characterized by dysregulated glucagon secretion. LY2409021, a potent, selective small-molecule glucagon receptor antagonist that lowers glucose was evaluated for efficacy and safety in patients with type 2 diabetes. RESEARCH DESIGN AND METHODSThe efficacy (HbA 1c and glucose) and safety (serum aminotransferase) of oncedaily oral administration of LY2409021 was assessed in two double-blind studies. Phase 2a study patients were randomized to 10, 30, or 60 mg of LY2409… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 33 publications
10
139
0
Order By: Relevance
“…Furthermore, all of these effects were pertussis toxindependent, but not sensitive to MEK inhibitors, demonstrating that the FKN/CX3CR1 pathway in hepatocytes signals through a classical G αi -coupled pathway to inhibit adenylate cyclase activity. It is interesting to note that FKN treatment decreased hepatic glucagon action without causing a compensatory increase in plasma glucagon levels or α cell hyperplasia, as occurs in glucagon receptor-KO mice or after chronic treatment with a glucagon receptor antagonist (55,57). Taken together with previously reported effects of the FKN/CX3CR1 system to improve hepatic fibrosis (58,59), our results support the idea that chronic FKN administration can improve glucose tolerance and hepatic function through direct hepatic actions.…”
Section: Flow Cytometry Analysis Of Cx3cr1 Expression In Primary Islesupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, all of these effects were pertussis toxindependent, but not sensitive to MEK inhibitors, demonstrating that the FKN/CX3CR1 pathway in hepatocytes signals through a classical G αi -coupled pathway to inhibit adenylate cyclase activity. It is interesting to note that FKN treatment decreased hepatic glucagon action without causing a compensatory increase in plasma glucagon levels or α cell hyperplasia, as occurs in glucagon receptor-KO mice or after chronic treatment with a glucagon receptor antagonist (55,57). Taken together with previously reported effects of the FKN/CX3CR1 system to improve hepatic fibrosis (58,59), our results support the idea that chronic FKN administration can improve glucose tolerance and hepatic function through direct hepatic actions.…”
Section: Flow Cytometry Analysis Of Cx3cr1 Expression In Primary Islesupporting
confidence: 87%
“…In T2DM, a lack of glucagon suppression leads to elevated levels of basal and postprandial glucagon, contributing to hyperglycemia (48)(49)(50)(51)(52). There are many studies showing the efficacy of inhibitory glucagon receptor antibodies to improve glucose tolerance in preclinical models and in some clinical studies (12,(53)(54)(55). Thus, the concept of targeting glucagon action to achieve hepatic insulin sensitivity and glucose lowering is well accepted (14), even though current methods of glucagon receptor inhibition may have unwanted side effects (56).…”
Section: Discussionmentioning
confidence: 99%
“…This is a seminal observation that was later confirmed by several independent research groups (Gerich et al, 1976;Felig et al, 1978;Butler and Rizza, 1991;Kelley et al, 1994). Subsequent studies showed that somatostatin-induced inhibition of postprandial glucagon secretion ameliorates hyperglycemia in patients with T2D (Gerich et al, 1974;Dinneen et al, 1995;Shah et al, 2000), and more recently that blocking glucagon action decreases hyperglycemia in a variety of species, including rodents (Mu et al, 2011;Kim et al, 2012b;Okamoto et al, 2017), rabbits (Brand et al, 1996), dogs (Rivera et al, 2007), nonhuman primates (Xiong et al, 2012;Okamoto et al, 2015), and humans (Petersen and Sullivan, 2001;Kelly et al, 2015;van Dongen et al, 2015;Kazda et al, 2016;Kostic et al, 2018). The virtues and limitations of antagonizing glucagon signaling for the treatment of diabetes have recently been highlighted in several review articles (Unger and Cherrington, 2012;Farhy and McCall, 2015;Lee et al, 2016b;Müller et al, 2017), with the implication that excess glucagon action can serve a greater role in the pathology of T2D than impaired insulin action (Unger and Cherrington, 2012).…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 91%
“…It is well established that GCGR deficiency or inhibition effectively lowers blood glucose in animal models of type 1 (4, 5) and type 2 diabetes (6-9). GCGR antagonism also blunts glucagon-stimulated glucose production in humans (10,11) and lowers blood glucose in healthy individuals and persons with type 2 diabetes (12)(13)(14)(15).…”
mentioning
confidence: 99%